Effect of foreign aid dependency on taxation revenue in Sub-Saharan Africa - Mbatia, Carolyne Nkatha (School of Economics, 2018)
There is an ongoing debate in the literature on the effect of foreign aid - concessional loans and grants - on fiscal tax revenues. Most scholars argue that loans have a positive effect on taxation revenue because of the obligation to repay them, whereas grants have a negative effect because the recipient treats them as 'free' money and as a substitute for taxation. This study focuses on the impact of foreign loans and grants on tax revenues for 42 Sub-Saharan African countries for the period 1990-2014. We test the above hypothesis for these African countries, but divide them into different income groups to account for underlying structural differences. Our results show that both concessional loans and grants have a negative effect on taxation revenue when all countries are pooled, and similarly for low-income and lower-middle income countries. As most of these countries received debt relief under the Highly Indebted Poor Country (HIPC) Initiative, we argue that recipient governments formulate an expectation of always receiving debt forgiveness and therefore treat both loans and grants as a "free" source of funds. This creates a disincentive to tax citizens who demand accountability for their taxes. However, upper-middle income countries (HICs) respond differently. Loans and grants have a positive effect on tax revenue in these countries. The effect of loans is a result of upper-income countries being ineligible for debt relief and therefore obligated to repay their loans, which creates an incentive to collect more taxes. The positive relationship between grants and tax revenue is explained by the fact that HICs have achieved a significant level of development, which translates to increased levels of efficiency and accountability in revenue systems from additional resources added to the fiscal. As a policy recommendation to address the disincentive created by grants, we argue that grants should be channeled through Non-Governmental Organisations (NGOs) or the private sector, rather than given directly to the governments.